Missing conformers. Comparative study of conformational cooling in cyanoacetic acid and methyl cyanoacetate isolated in low temperature inert gas matrixes - Reva, I. D. (2003)
A comparative conformational study of two related systems, methyl cyanoacetate (MCA) and cyanoacetic acid (CAA), is presented. Ab initio calculations predicted that both systems have two nearly isoenergetic conformers separated by similar low energy barriers (about 3 kJ mol-1). In xenon matrixes deposited at temperatures above 40 K for MCA and above 20 K for CAA only one conformer was observed for each of the two systems. However, below those temperatures two MCA and two CAA conformers were trapped into the matrixes. Conformational cooling was found responsible for this behavior. Factors contributing to this effect are discussed.